Cesarean section thromboprophylaxis in the context of the modern ERAC rapid recovery concept (Perioperaciina Medicina, 2019)
This article outlines the main guidelines of the European Society of Anesthesiologists for Perioperative Venous Thromboembolism Prevention and the basic guidelines of the Society for Obstetric Anesthesia and Perinatology (SOAP) for Enhanced Recovery After Cesarean (ERAC). The search for effective methods of recovery after caesarean section, the desire to reduce the risks of postoperative complications, to shorten the length of the hospital stay led us to the introduction of the modern concept of rapid recovery. The concept of Enhanced Recovery After Cesarean is already used in the “Leleka” maternity hospital. The positive results of the implementation of the ERAC concept in obstetric practice make it necessary to modernize the traditional approach to the postoperative period.
Keywords: preoperative period; thromboprophylaxis; caesarean section